2021
DOI: 10.1364/ol.415475
|View full text |Cite
|
Sign up to set email alerts
|

Strong light emission from a defective hexagonal boron nitride monolayer coupled to near-touching random plasmonic nanounits

Abstract: In this Letter, we demonstrate strong light emission from defective hexagonal boron nitride (hBN) defect centers upon their coupling with disorder near-touching plasmonic units. Based on numerical simulations and characterization results, the plasmonic design at thin layer thicknesses of 20 nm can provide above 2 orders of magnitude enhancement in photoluminescence (PL) spectra. Moreover, this plasmonic platform shortens the luminescence lifetime of the emitters. The proposed design can be easily extended to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…To realize this design architecture, oblique angle deposition using a thermal evaporator is adopted to grow Au nanoislands on a quartz substrate. The details of this process are provided in our previous study [24]. In this method, due to the atomic shadowing effect, the layer tends to grow as nanoisland configurations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To realize this design architecture, oblique angle deposition using a thermal evaporator is adopted to grow Au nanoislands on a quartz substrate. The details of this process are provided in our previous study [24]. In this method, due to the atomic shadowing effect, the layer tends to grow as nanoisland configurations.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in thicker layers, only the largest islands continue their growth, while in thinner layers, we can have multiple-size particles. In addition, it is found that, in neartouching plasmonic particles, smaller dimensions generate a stronger field enhancement [24]. Taking all into account, the Au nanoislands height is adopted in a nominal value of 20 nm.…”
Section: Resultsmentioning
confidence: 99%
“…1) In this context, great efforts have been made to develop perfect absorbers operating in the MWIR regime, which could inspire a vast variety of potential applications including thermal photovoltaics, 2) thermal bolometers, 3) infrared sensing, 4) infrared camouflage, 5,6) infrared photodetector, 7) radiative cooling, 8) and thermal emitters, 9,10) etc. For these purposes, many nanostructured optical systems were developed in various sizes, shapes and architectures to attain perfect absorbers, [11][12][13][14][15][16][17][18][19][20] such as plasmonic metasurfaces, optical cavities, metallic gratings and photonic crystals. However, the fabrication processes of such nanostructured absorbers usually require high precision and costly lithography techniques such as electron-beam lithography, which makes them difficult for massive industrial manufacturing and hence limiting their practical applications.…”
mentioning
confidence: 99%